Case management as an opportunity for healthcare: user experiences - Lorena Chaparro-Díaz; Cindy Lorena Valbuena-Castiblanco; Sonia Carreño-Moreno; Sandra Milena Hernández-Zambrano; Ana Julia Carrillo-Algarra (Universidad de Santander, 2023)
Introduction: People with multimorbidity and their caregivers are beginning to be recognized as emerging subjects of health systems. In Colombia there is no differentiated approach to care for this population, as well as its health-disease process. Objective: To understand the experience of people with multimorbidity and their caregivers after receiving a case management intervention. Methods and materials: It is a qualitative study in which 33 participants among people with multimorbidity and their caregivers who received intervention with case managers were interviewed, a comparative analysis and use to tools analytics grounded theory. Results: There are 3 dimensions that are, the actors where nursing becomes relevant as a reliable source of care; the Care Meeting, as a space created within case management to maintain trust and; Results in the health system, where the need to integrate this type of outbreak into the Colombian Health Model is confirmed. Discussion: Complementary qualitative evidence data from the central study with a greater impact on the quality of care through the therapeutic relationship at home. Conclusion: The dyad requires home support for self-management of the disease based on trust, empathy, empowerment and administrative management carried out by case managers.